Duchowość inkarnacyjna i jej chrystologiczne podstawy - Sawa, Przemysław (Śląskie Studia Historyczno-Teologiczne, 2011)
The Christian type of spirituality is defined by participation in God through Jesus, the incarnate Son of God. The attitude of a human being towards God, the world, other people and himself results from the degree of acceptance of the truth about God who reveled himself through Jesus. As a consequence, spirituality has its deep roots in the christological dogma. The fact that Jesus took on a human body and nature and became both a man and God lies in the centre of the New Testament proclamation. This reality makes Christianity peculiar as the divinity does not contradict the humanity; God does not pose a threat to a human being, to his freedom or identity. The difference between sacredness (sacrum) and profanity (profanum) virtually vanishes. In other words, sacred permeates secular thanks to the Incarnation, which materializes spirituality (this can be seen in the reality of Church, Sacraments, the service of love or iconography). In addition, the intimacy of ‘devine’ and ‘human’, profoundly fulfilled by the Incarnation of Logos (Word), underlines the beauty of a human body. Making an analogy between a human being and Jesus Christ, it can be said that there is one person and two quasi-natures: material-carnal and spiritual. They remain separate and do not constitute a third reality, but the Person is the one that unites them. In this way, the truth about the personal union and two natures of Christ becomes a model in finding out the truth about the human being. The Incarnation of Logos (Word) with the proclamation of the value of human life designates Christian model of spirituality as the incarnational spirituality. This model shows the necessity to strike an essential balance in life. At the same time, a certain outlook on life and world is created through the prism of the Incarnated. What is more, the Incarnation of Logos determines various spheres of life showing its purpose and forms of its recognition and expression (orthodoxy is connected with ortopraxy). Bearing a Christological model in mind, it is necessary to develop your faith everyday upon this model. What is meant here is having a purpose in life (theosis, eternity), experiencing everyday life properly (human culture, worldliness) and joining all these activities with the Christian cult. Incarnational spirituality is also connected with the relaxed attitude to the material world, where the human being has been placed (culture). Finally, incarnational and anthropological model gives direction to Christian piety, prayers and faith incorporating coexistence of spiritual and material aspects. Invisible and inner matters function together with the visible and outer ones.